Innovation in Smart Ports: Future Directions of Digitalization in Container Ports - Heikkilä Marikka; Saarni Jouni; Saurama Antti (MDPI, 2022)
New digital Industry 4.0 solutions and smart applications are being adopted in many industries, also in the most advanced ports in the world. Still, it is not clear in which directions digitalization in ports will develop in the future. Building on the research literature and the state-of-the-art in major container ports, this research characterizes smart ports and Port 4.0 with three key focus areas: automation, sustainability and collaboration. Following the scenario building theory, this article constructs four alternative scenarios for future smart ports and shows the ways in which these alternative scenarios will lead to different prioritization of digital innovations between automation, sustainable development and cooperation issues. This will have a big impact on what digitalization in ports will be like in the future